Biodiversity Studies Of Extreme Halophiles Isolated From Little Rann Of Kutch - MRUGESH KHUNT,; NEEPA PANDHI, (International Journal of Pharma and Bio Sciences, 2012)
Altogether, 30 extreme halophiles were isolated from salt, mud and water samples collected from little rann of Kutch, designated as Ku-1 to Ku-30. All the organisms were Gram positive or Gram variable, non capsulated and highly diversified in terms of colony morphology, size, shape, arrangement and biochemical properties. The data indicates that little Rann of Kutch having rich halophilic microbial diversity. All the isolates were able to produce extracellular lipases; 10 produce proteases, 9 produce amylases and none of them able to produce cellulases and chitinases